2023
DOI: 10.1038/s41467-023-42064-1
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater sequencing reveals community and variant dynamics of the collective human virome

Michael Tisza,
Sara Javornik Cregeen,
Vasanthi Avadhanula
et al.

Abstract: Wastewater is a discarded human by-product, but its analysis may help us understand the health of populations. Epidemiologists first analyzed wastewater to track outbreaks of poliovirus decades ago, but so-called wastewater-based epidemiology was reinvigorated to monitor SARS-CoV-2 levels while bypassing the difficulties and pit falls of individual testing. Current approaches overlook the activity of most human viruses and preclude a deeper understanding of human virome community dynamics. Here, we conduct a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 36 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…SARS-CoV-2, Influenza, and Mpox) correlate to clinical case data. 17 Seasonal influenza serotypes H3N2 and H1N1 are routinely detected in TEPHI wastewater samples, and levels have corresponded to clinical case loads from May 2022 through the beginning of March 2024. Until that point, serotype H5N1 was never detected (0 out of 1,337 wastewater samples).…”
Section: Main Text and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2, Influenza, and Mpox) correlate to clinical case data. 17 Seasonal influenza serotypes H3N2 and H1N1 are routinely detected in TEPHI wastewater samples, and levels have corresponded to clinical case loads from May 2022 through the beginning of March 2024. Until that point, serotype H5N1 was never detected (0 out of 1,337 wastewater samples).…”
Section: Main Text and Resultsmentioning
confidence: 99%
“…All collection, processing, and sequencing methods have been described in an earlier publication 17 and were followed precisely. To restate, between 100–500 mL of raw wastewater influent was collected into 500 ml leak-proof prelabeled sample bottles at 23 wastewater treatment plants in 10 Texas cities, the identities of these cities are masked on the request of local public health officials and water utilities.…”
Section: Methodsmentioning
confidence: 99%
“…Opportunities for technical advancement include (1) increasing the enrichment factor via changes to hybridization conditions or new chemistry that strengthens hybridization, (2) eliminating probes that capture highly abundant off-target sequences, both during in silico panel design and during panel testing specifically on wastewater samples, (3) balancing the number of probes specific for prevalent viruses and rare viruses based on empirical data from wastewater monitoring, and/or designing custom panels that exclude high-abundance targets, (4) enabling transparency and optimization by embracing open source rather than proprietary panel designs, using available bioinformatic tools. 16,45 (e.g., Kraken2, 46 Centrifuge 47 ), combined mapping and assembly/consensus-building tools (e.g., EsViritu, 29 IDSeq, 48 and DRAGEN, 49 among others), and de novo assembly followed by homology searches (e.g., BLAST, Hidden Markov Model searches (HMMs)). The diversity of approaches reflects the many different goals of wastewater virus sequencing ranging from fast classification of reads to variant tracking to the discovery of novel viruses.…”
Section: Considerations and Challengesmentioning
confidence: 99%
“…Child et al applied both RVOP and RPIP in parallel and reported lower coverage of SARS-CoV-2 with RPIP, likely due to competition for sequencing with other targets . Several other studies applied very broad panels covering major groups of human viruses and reported that the predominant human virus was Mamastrovirus followed by other enteric viruses, while respiratory viruses were at lower relative abundance sometimes by orders of magnitude. , , Although differences in samples, sample processing, and bioinformatics make direct comparisons impossible (Table ), these results point to trade-offs in probe panel selection.…”
Section: Probe Set Selection Hybridization and Sequencing Depthmentioning
confidence: 99%
See 1 more Smart Citation